A Dictionary of Contemporary World History : From 1900 to the Present Day - Palmowski, Jan (Oxford, New York Oxford University Press, 2003)
A searchable database providing in-depth coverage of the major historical figures and events from 1900 to the present day. Extensive surveys of every country are included with detailed analytical entries covering political and military leaders, political parties, international organizations, and acts of war.
Keywords: History, Modern -- History, Modern -- 20th century -- Dictionaries